Some analytical characteristics of the distribution of land : an exercise in graduation by the lognormal, gamma, and logamma laws - Krishnaji, N. (Working paper (Centre for Development Studies (Trivandrum, India)), 1974)
With reference to the states of India, 1961-1962.